Al-Tahlīl fī Dirāsah Manhaj Tadrīs Mahārah al-Kalām fī Kitāb Ta’līm Aa-Lugah Al-‘Arabiyyah - Robbianto, Muhammad; Suharto, Toto; Qosim, Muhammad Nanang (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research is to (1) describe the application of the curriculum for teaching speaking skills in the Arabic language teaching book for the second intermediate grade of the Indonesian Ministry of Religious Affairs in 2020. (2) to describe the advantages and disadvantages of the curriculum for teaching speaking skills in the Arabic language teaching book for the second intermediate grade. (3) knowing how to analyze the curriculum for teaching speaking skills in the book on teaching the Arabic language for the second intermediate grade. This research is based on descriptive analysis methods. This research indicates that the book's approach to teaching speaking skills includes four elements: objectives, content, teaching methods, and evaluation. Data collection techniques used in this research include the collection of data sources, data collection, data analysis, and interpretation of results. As a consequence of this study, the book's speaking skill teaching methodology consists of four components: objectives, content, teaching strategies, and evaluation. These are the outcomes of the examination of the book's speaking skills training method: that the information is acceptable based on the criteria of excellent content, the listening, speaking, reading, and writing abilities are presented in a good order, Data analysis techniques used in this research: Data limitations, data display, and conclusions, and the core and fundamental competencies meet the requirements of good competence. With a disclaimer that neither at the middle nor after the semester does this book assess speaking abilities due to its usage of an intermediate language.